Aquaponics hegemony: An invitation of practice (Research, Society and Development, 2024)
Faced with environmental challenges and the growing demand for healthy food, this review aims to present aquaponics as a viable solution to minimize water consumption, reduce environmental pollution, and mitigate soil degradation. The review highlights the importance of overcoming traditional agricultural paradigms and adopting more ecological practices. A detailed analysis of the development and application of aquaponics was conducted, as well as its advantages over conventional methods and different technological approaches, such as the DWC (Deep Water Culture) system. Additionally, technical and economic variables that may influence the success of aquaponics were discussed, along with the possibilities of integrating new technologies and automation practices. The results show that aquaponics uses up to 90% less water compared to traditional methods and can be implemented in reduced spaces, including urban areas and arid regions. The review also emphasizes the need for interdisciplinary knowledge for the effective operation of the system, highlighting the potential of aquaponics to produce high-quality organic food with greater added value. It is concluded that aquaponics represents a promising solution for sustainable food production, with significant economic and ecological benefits, especially when integrated with public policies aimed at food security.